Depicting Residential Night Flow - Barreto, D. (2010)
This article presents the results of studies conducted in three different localities in São Paulo with the intention of obtaining the intake times in single-family and multifamily economies. Measurements were made through the use of equipment for data acquisition instrumentation and water meters. The resulting data were treated to obtain information about the specific water consumption and the residential minimum night flow (MNF). The monitored residences are located in areas west and east of Sao Paulo city. The results pointed out the values of minimum night flows for two types of buildings: homes (one storey) and apartments (multistory). For residences the average MNF was 2,34 L/h. For apartments the average MNF was 2,7 L/h. Both were recorded at 3:00 am. In a study conducted in Spain, these values of MNF were 4,0 L/h for homes and 8,0 L/h for apartments and these occurred between 3:00 and 4:00 pm. For the home was monitored the points of use and could be identified the sanitary appliances that were used by residents in the schedule which includes the NMF (2:00 5:00). The devices most commonly used at this time were: the shower and lavatory faucet. Observations on the values found indicate that there are real uses of sanitary appliances in homes and there are still portions of consumption to be identified that may be due to leaks that can be avoided through education campaigns. It was also the occurrence of flow in the limit of very small flow of water meters transition entailing the systematic occurrence of sub-metering that can affect the calculation of apparent losses.